Entomologic investigation of Plasmodium knowlesi vectors in Kuala Lipis, Pahang, Malaysia - Jiram, A.; Vythilingam, I.; NoorAzian, Y.; Yusof, Y.; Azahari, A.; Fong, M.Y. (2012)
ABSTRACT: BACKGROUND: The first natural infection of Plasmodium knowlesi in humans was recorded in 1965 in peninsular Malaysia. Extensive research was then conducted and it was postulated that it was a rare incident and that simian malaria will not be easily transmitted to humans. However, at the turn of the 21st century, knowlesi malaria was prevalent throughout Southeast Asia and is life threatening. Thus, a longitudinal study was initiated to determine the vectors, their seasonal variation and preference to humans and macaques. METHODS: Monthly mosquito collections were carried out in Kuala Lipis, Pahang, peninsular Malaysia, using human-landing collection and monkey-baited traps at ground and canopy levels. All mosquitoes were identified and all anopheline mosquitoes were dissected and the gut and gland examined for oocysts and sporozoites. Nested polymerase chain reaction (PCR) was conducted on positive samples, followed by sequencing of the csp gene. RESULTS AND DISCUSSION: Anopheles cracens was the predominant mosquito biting humans as well as the macaques. It comprised 63.2 of the total collection and was the only species positive for sporozoites of P. knowlesi. It was exophagic and did not enter houses. Besides An. cracens, Anopheles kochi was also found in the monkey-bait trap. Both species preferred to bite monkeys at ground level compared to canopy. CONCLUSION: Anopheles cracens, which belongs to the Dirus complex, Leucosphyrus subgroup, Leucosphyrus group of mosquitoes, has been confirmed to be the only vector for this site from Pahang during this study. It was the predominant mosquito at the study sites and with deforestation humans and villages are entering deeper in the forests, and nearer to the mosquitoes and macacques. The close association of humans with macaques and mosquitoes has led to zoonotic transmission of malaria.